Effectiveness of ozonation in decomposition of clofibric acid and bisphenol a in model water solutions = Skuteczność ozonowania w rozkładzie kwasu klofibrowego i bisfenolu A w modelowych roztworach wodnych - Zacharska, Ewa; Odrzywolski, Adam; Depta, Marcin; Ozonek, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article contains a brief characteristic of the compounds counted among PPCPs (Pharmaceuticals and Personal Care Products) and EDCs (Endocrine Disrupting Compounds) along with the presentation of their removal methods used in typical WWTPs (Wastewater Treatment Plants), WTPs (Water Treatment Plants) as well as different methods examined in laboratory conditions.
Keywords: związki PPCP; ozonowanie; PPCPs; clofibric acid; ozonation